2009
DOI: 10.5465/amr.2009.44885978
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Path Dependence: Opening the Black Box.

Abstract: To enable a better understanding of the underlying logic of path dependence, we set forth a theoretical framework explaining how organizations become path dependent. At its core are the dynamics of self-reinforcing mechanisms, which are likely to lead an organization into a lock-in. By drawing on studies of technological paths, we conceptualize the emergent process of path dependence along three distinct stages. We also use the model to explore breakouts from organizational path dependence and discuss implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
969
3
43

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 799 publications
(1,093 citation statements)
references
References 69 publications
20
969
3
43
Order By: Relevance
“…Influenced by decisions made in other critical moments, path dependence ensures a regime that governs self-reinforcing feedback as a specific pattern of social practices, which gain more and more dominance over the alternatives. Finally, path dependence may cause organizational lock-in, restricting future decision-making (Sydow et al, 2009). Sydow et al (2009) identified three levels for investigation, specifically, the individual level, the network level and the field level.…”
Section: Organizational Path Dependencementioning
confidence: 99%
See 2 more Smart Citations
“…Influenced by decisions made in other critical moments, path dependence ensures a regime that governs self-reinforcing feedback as a specific pattern of social practices, which gain more and more dominance over the alternatives. Finally, path dependence may cause organizational lock-in, restricting future decision-making (Sydow et al, 2009). Sydow et al (2009) identified three levels for investigation, specifically, the individual level, the network level and the field level.…”
Section: Organizational Path Dependencementioning
confidence: 99%
“…Finally, path dependence may cause organizational lock-in, restricting future decision-making (Sydow et al, 2009). Sydow et al (2009) identified three levels for investigation, specifically, the individual level, the network level and the field level. The next subsection, in which we discuss path-dependence in supply chains is concerned with the field level.…”
Section: Organizational Path Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…Paths are usually implicitly conceptualized as persistent patterns in the development of a technology, a company or an industry (Cowan and Gunby, 1996;Rycroft and Kash, 2002;Sydow et al, 2009). Even if the early stages of path dependency allow for some degree of variety, by later phases there is only one path left; the number of alternative choices gradually decreases (David, 1985;Arthur, 1989;Cowan and Gunby, 1996) until companies or entire industries become locked-in to one -often inferioroption, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Higher fees in financial centers may also be due to path dependence and lock-in effects (Krugman, 1991;Martin and Sunley, 2006;Sydow et al, 2009). 4 For the mutual fund industry, this may imply that funds are domiciled in Luxembourg because the structures necessary to set up such funds already exist in this country and not because of a favorable environment for the mutual fund industry.…”
Section: Introductionmentioning
confidence: 99%